2002
DOI: 10.1021/jp022106h
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Surfactants at the Gas/Solution Interface of Cavitation Bubbles:  An Ultrasound Intensity-Independent Frequency Effect in Sonochemistry

Abstract: A major limitation in determining the effects of ultrasound frequency in sonochemistry in relation to cavitation is that no reliable relationship exists between the energy supplied to the system and the energy converted by the cavitation process in producing a sonochemical effect. However, the current study presents a frequency effect that is independent of the energy supplied to the system. Spin-trapping of secondary carbon radicals with 3,5-dibromo-4-nitrosobenzenesulfonic acid-d 2 (DBNBS-d 2 ) and electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
115
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(134 citation statements)
references
References 76 publications
19
115
0
Order By: Relevance
“…Sostaric and Riesz [26] indicated that the Fe 3+ yield at 354 kHz for 3 min under argon gas increased with an increase in power up to a plateau (50-60 W).…”
Section: Effect Of Acoustic Powermentioning
confidence: 99%
“…Sostaric and Riesz [26] indicated that the Fe 3+ yield at 354 kHz for 3 min under argon gas increased with an increase in power up to a plateau (50-60 W).…”
Section: Effect Of Acoustic Powermentioning
confidence: 99%
“…There was no possibility for the direct interaction between ultrasound and substance, and in such a way it is an indirect phenomenon, so that cavitation must be facilitated to encourage a chemical reaction. Hence, the make use of ultrasound to enhance chemical reactivity [24,25] is now familiar as a feasible environmental safe alternative machinery. Kinetics of the reaction in synthesizing 3,5-dimethyl-1-(3-phenylpropyl)-1H-pyrazole, such as agitation speed, amount of catalyst, quaternary ammonium salts, amount of sodium hydroxide and temperature on the conversion were investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…While the sonolysis of surfactant has been extensively examined [9][10][11][12][13][14][15][16][17][18], the behavior of surfactants during acoustic cavitation is still unclear. For example, Yang et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…reported the sonochemical degradation of the surfactants, alkyl acids and alkyl amines, where they discussed mainly the effects of the alkyl chain length of the solute and the pH of the solution on the intensity of sonoluminescence. In addition, the spin-trapping studies by Sostaric and Riesz [16,17] showed that anion surfactants with shorter alkyl chain length were more efficiently accumulated at the cavitation bubble interface under continuous sonication. Based on previous reports [10,16,17], it is suggested that the degradation rates of anion surfactants are affected by their alkyl chain length.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation